Strength and conditioning for combat sports athletes - Emerson Franchini; Tomás Herrera-Valenzuela (Universidad de León, 2021)
Editors • Emerson Franchini - University of São Paulo, São Paulo (Brazil) • Tomás Herrera-Valenzuela - Universidad de Santiago de Chile (Chile)  Authors • Ursula Ferreira Julio - University of São Paulo, São Paulo (Brazil) • Emerson Franchini - University of São Paulo, São Paulo (Brazil) • Tomás Herrera-Valenzuela - Universidad de Santiago de Chile (Chile) • João Paulo Lopes-Silva - CESMAC University Centre (Brazil) • Braulio Henrique Magnani Branco - Cesumar University (Brazil) • Jonatas Ferreira da Silva Santos - Federal University of the Jequitinhonha and Mucuri Valleys (Brazil) • Rubens Santos-Junior - State University of Pará (Brazil)  Reviewers • Filipa Almeida - Universidad de Granada (Spain) • Juan Bonitch Góngora - Universidad de Granada (Spain) • Eduardo Carballeira Fernández - Universidade da Coruña (Spain) • Daniele Detanico - Universidade Federal de Santa Catarina (Brazil) • Raquel Escobar Molina - Universidad de Granada (Spain) • Matheus Hausen - Brazil Olympic Committee (Brazil) • Raquel Hernandez García - Universidad de Murcia (Spain) • Eliseo Iglesias Soler - Universidade da Coruña (Spain) • Carlos Montero Carretero - Universidad Miguel Hernández (Spain) • Emanuela Pierantozzi - Università degli Studi di Genova (Italy) • Luis Santos Rodríguez - Universidad de León (Spain) • Jozef Simenko - University of Essex (UK)